Genomic consequences of transitions from cross- to self-fertilization on the efficacy of selection in three independently derived selfing plants - Ness, Rob W (BioMed Central, 2012)
BACKGROUND: Transitions from cross- to self-fertilization are associated with increased genetic drift rendering weakly selected mutations effectively neutral. The effect of drift is predicted to reduce selective constraints on amino acid sequences of proteins and relax biased codon usage. We investigated patterns of nucleotide variation to assess the effect of inbreeding on the accumulation of deleterious mutations in three independently evolved selfing plants. Using high-throughput sequencing, we assembled the floral transcriptomes of four individuals of Eichhornia (Pontederiaceae); these included one outcrosser and two independently derived selfers of E. paniculata, and E. paradoxa, a selfing outgroup. The dataset included ~8000 loci totalling ~3.5 Mb of coding DNA. RESULTS: Tests of selection were consistent with purifying selection constraining evolution of the transcriptome. However, we found an elevation in the proportion of non-synonymous sites that were potentially deleterious in the E. paniculata selfers relative to the outcrosser. Measurements of codon usage in high versus low expression genes demonstrated reduced bias in both E. paniculata selfers. CONCLUSIONS: Our findings are consistent with a small reduction in the efficacy of selection on protein sequences associated with transitions to selfing, and reduced selection in selfers on synonymous changes that influence codon usage.